Evaluation of Airway Volume in Cleft Lip and Palate Following Nasoalveolar Molding - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Patients with cleft lip and palate (CLP) have commonly reduced nasal airways and are more prone to snoring, mouth breathing and hypopnea during sleep. Therefore, the morphometric evaluation of pharyngeal airway in patients with CLP is crucial. The purpose of this study is to evaluate the pharyngeal airway volumes of patients with CLP who underwent nasoalveolar molding (NAM) and to compare them with a well-matched control group without NAM. The study consisted of 40 patients with CLP divided into 2 main groups (26 with NAM; 14 without NAM) and 4 subgroups (15 unilateral CLP [UCLP] with NAM, mean age: 10.13 +/- 1.30 years; 11 bilateral CLP [BCLP] with NAM, mean age: 10.55 +/- 1.51 years; 7 UCLP without NAM, mean age: 9.86 +/- 1.68 years; 7 BCLP without NAM, mean age: 10.28 +/- 1.89 years). Nasopharyngeal, oropharyngeal, and total airway volumes of all the patients were calculated 3-dimensionally with cone-beam computed tomography. There were statistically significant differences in nasopharyngeal volume (P< 0.05) of NAM group compared to control group; however, volumetric differences in oropharyngeal and total pharyngeal airway were not significant (P> 0.05). The amount of nasopharyngeal, oropharyngeal, and total pharyngeal airway size in the BCLP with NAM group was significantly larger compared to BCLP without NAM group (P< 0.05). However, UCLP did not show any significant difference in NAM group (P> 0.05). This study implies that NAM can effectively enlarge the nasopharyngeal airway size in patient with CLP. In addition, the pharyngeal airway volume enlargement is more apparent in BCLP than UCLP individuals.
Keywords: Cleft lip and palate; cone-beam computed tomography; nasoalveolar molding; MAXILLARY ARCH DIMENSIONS; OBSTRUCTIVE SLEEP-APNEA; INFANT ORTHOPEDICS; NASAL AIRWAY; THERAPY; MORPHOLOGY; GROWTH; CHILDREN; SIZES; NAM